Congenital immobility and stiffness related to biallelic ATAD1 variants. (December 2020) - Bunod, Roxane; Doummar, Diane; Whalen, Sandra; Keren, Boris; Chantot-Bastaraud, Sandra; Maincent, Kim; Villy, Marie-Charlotte; Mayer, Michèle; Rodriguez, Diana; Burglen, Lydie; Léger, Pierre-Louis; Kieffer, François; et al.
Abstract : Objective: To delineate the phenotype associated with biallelic ATAD1 variants. Methods: We describe 2 new patients with ATAD1 -related disorder diagnosed by whole-exome sequencing and compare their phenotype to 6 previous patients. Results: Patients 1 and 2 had a similar distinctive phenotype comprising congenital stiffness of limbs, absent spontaneous movements, weak sucking, and hypoventilation. Both had absent brainstem evoked auditory responses (BEARs). Patient 1 carried the homozygous p.(His357Argfs*15) variant in ATAD1 . In the light of the finding in patient 1, a second reading of exome data for patient 2 revealed the novel homozygous p.(Gly128Val) variant. Conclusions: Analysis of the phenotypes of these 2 patients and of the 6 previous cases showed that biallelic ATAD1 mutations are responsible for a unique congenital encephalopathy likely comprising absent BEAR, different from hyperekplexia and other conditions with neonatal hypertonia.